Comparative Genomics and Transcriptomics During Sexual Development Gives Insight Into the Life History of the Cosmopolitan Fungus Fusarium neocosmosporiellum - Kim, Wonyong; Cavinder, Brad; Proctor, Robert H.; O’Donnell, Kerry; Townsend, Jeffrey P.; Trail, Frances (Frontiers in Microbiology, 2019)
Fusarium neocosmosporiellum (formerly Neocosmospora vasinfecta) is a cosmopolitan fungus that has been reported from soil, herbivore dung, and as a fruit- and root-rot pathogen of numerous field crops, although it is not known to cause significant losses on any crop. Taking advantage of the fact that this species produces prolific numbers of perithecia in culture, the genome of F. neocosmosporiellum was sequenced and transcriptomic analysis across five stages of perithecium development was performed to better understand the metabolic potential for sexual development and gain insight into its life history. Perithecium morphology together with the genome and transcriptome were compared with those of the plant pathogen F. graminearum, a model for studying perithecium development. Larger ascospores of F. neocosmosporiellum and their tendency to discharge as a cluster demonstrated a duality of dispersal: the majority are passively dispersed through the formation of cirrhi, while a minority of spores are shot longer distances than those of F. graminearum. The predicted gene number in the F. neocosmosporiellum genome was similar to that in F. graminearum, but F. neocosmosporiellum had more carbohydrate metabolism-related and transmembrane transport genes. Many transporter genes were differentially expressed during perithecium development in F. neocosmosporiellum, which may account for its larger perithecia. Comparative analysis of the secondary metabolite gene clusters identified several polyketide synthase genes that were induced during later stages of perithecium development. Deletion of a polyketide synthase gene in F. neocosmosporiellum resulted in a defective perithecium phenotype, suggesting an important role of the corresponding metabolite, which has yet to be identified, in perithecium development. Results of this study have provided novel insights into the genomic underpinning of development in F. neocosmosporiellum, which may help elucidate its ability to occupy diverse ecological niches.